GDP-related emission targets weaknesses: The case of Argentina - Mariana Conte Grand (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2016)
GDP linked targets have the potential to favor green growth and avoid "hot air" in uncertain backgrounds, like those of many developing economies. Even if they are not a guarantee of emissions reduction as required by the 2 degree Celsius Copenhagen goal because emissions' intensity can decrease even when emissions do not. A few countries have submitted at some point of international negotiations a target based on this type of metric. Argentina is one of them, together with Chile, China, India, Singapore, Tunisia, Uruguay and Turkmenistan. As is the case of all target forms, it requires good monitoring and forecast of emissions. But, as the literature has shown, one of the GDP-related target weaknesses is that it relies on a second indicator: the GDP. This article shows concretely how GDP biases influence intensity targets monitoring, using as a base the case of Argentina.
Keywords: 330; climate change; intensity targets; target metrics; developing countries; Latin America; Argentina